(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
Ten bacterial isolates were successfully isolated from pristine and contaminated areas in Malaysia. There was no lag phase observed signifying each of these isolates was able to quickly induce cellular machinery for diesel assimilation. The best isolate was tentatively identified as Bacillus sp. strain MO1 based on carbon utilisation profiles using Biolog GP plates and partial 16S rDNA matching. Strain MO1 grew optimally at 37 oC on 4% (v/v) diesel, pH 7.5 and 0.9% (w/v) KNO3. Diesel components were proven to be completely eliminated from the reduction in the hydrocarbon peaks monitored by gas chromatographic analysis after 6 days of incubation. The bacterium was found to be a better remediation agent than a commercial bioremediation product. All of these characteristics suggest that this bacterium is the suitable bacterium for bioremediation of diesel spills and pollution in the tropics.